2020
DOI: 10.2147/cmar.s279712
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Abnormal Cervical Lesions and Associated Factors Among Women in Harar, Eastern Ethiopia</p>

Abstract: Purpose: The primary objective of this study was to determine the prevalence of abnormal cervical lesions and associated factors and the secondary objective was to assess adherence to post-cryotherapy treatment recommendations, among women in Harari region, eastern Ethiopia. Materials and Methods: This study was conducted in two public hospitals in Harar city from January 1 to May 30, 2019. A facility-based descriptive cross-sectional study was conducted and a total of 1181 women were included in the study. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Women having STI had 3.5 times higher odds of developing precancerous cervical lesions compared to women with no history of STI [AOR) = 3.46(95%CI:1.94-6.18)], which is similar to research conducted in the Debre Markos town, 30 Southern Ethiopia, 25 and three referral hospital in Amhara region. 5 This association might be due to that the fact that cervical cancer occurs in the cervix, which is the entrance to the uterus.…”
Section: Discussionsupporting
confidence: 74%
“…Women having STI had 3.5 times higher odds of developing precancerous cervical lesions compared to women with no history of STI [AOR) = 3.46(95%CI:1.94-6.18)], which is similar to research conducted in the Debre Markos town, 30 Southern Ethiopia, 25 and three referral hospital in Amhara region. 5 This association might be due to that the fact that cervical cancer occurs in the cervix, which is the entrance to the uterus.…”
Section: Discussionsupporting
confidence: 74%
“…Studies revealed the uptake of cervical cancer screening in sub-Saharan Africa was 12.87%; 15 in Botswana, 72% of the women screened for cervical cancer ever by Pap smear; 16 20.6% of the women in Uganda screened for cervical cancer; 17 in other studies, only 29% screened for cervical cancer; 18 in a study conducted in Kenya, 16.4% of women screened; 19 and in Hara region, Ethiopia, 24.5% screened. 20 Furthermore, the previous study in Kenya showed that 46% screened; 21 in Guraga zone, Ethiopia, only 3.8% screened; 22 in Urban areas, Somali, 32.7% tested; 23 and other national level studies conducted in Kenya indicated that (19.4%) of women screened, 24 and only 5% underwent screening. 25 Determinants identified in previous literature with the uptake of cervical cancer were age, 19,[26][27][28] residence, 19,29 marital status, 28,30 occupation, 19,29 educational status, 15,19,20 wealth, 17,19,30 knowledge on cervical cancer, 15,17,25,31 age at first sex, 22,28,32 human immune deficiency virus status, 15,25,33 and awareness.…”
Section: Introductionmentioning
confidence: 94%
“…20 Furthermore, the previous study in Kenya showed that 46% screened; 21 in Guraga zone, Ethiopia, only 3.8% screened; 22 in Urban areas, Somali, 32.7% tested; 23 and other national level studies conducted in Kenya indicated that (19.4%) of women screened, 24 and only 5% underwent screening. 25 Determinants identified in previous literature with the uptake of cervical cancer were age, 19,[26][27][28] residence, 19,29 marital status, 28,30 occupation, 19,29 educational status, 15,19,20 wealth, 17,19,30 knowledge on cervical cancer, 15,17,25,31 age at first sex, 22,28,32 human immune deficiency virus status, 15,25,33 and awareness. 17,20,22,[25][26][27] Besides, other literature identified awareness on services, 23,27 history of STI, 27,[32][33][34] multiple sexual partners, 20,…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations